Exploring halide destabilised calcium hydride as a high-temperature thermal battery - Sofianos, M. Veronica; Randall, Samuel; Paskevicius, Mark; Aguey-Zinsou, K.F.; Rowles, Matthew; Humphries, Terry; Buckley, Craig (ELSEVIER SCIENCE SA, 2020)
© 2019